Effect of Noise Intensity and Illumination Intensity on Visual Performance. Issue 2 (October 2014) - Lin, Chin-Chiuan
The results of Experiment 1 indicated that noise and illumination intensity have a significant effect on character identification performance, which was better at 30 dBA than at 60 and 90 dBA, and better at 500 and 800 lux than at 200 lux. However, the interaction of noise and illumination intensity did not significantly affect visual performance. The results of Experiment 2 indicated that noise and illumination intensity also had a significant effect on reading comprehension performance, which was better at 30 dBA than at 60 and 90 dBA, and better at 500 lux than at 200 and 800 lux. Furthermore, reading comprehension performance was better at 500 lux lighting and 30 dBA noise than with 800 lux and 90 dBA. High noise intensity impaired visual performance, and visual performance at normal illumination intensity was better than at other illumination intensities. The interaction of noise and illumination had a significant effect on reading comprehension. These results indicate that noise intensity lower than 30 dBA and illumination intensity approximately 500 lux might be the optimal conditions for visual work.